Effects of amikacin, polymyxin-B, and sulbactam combination on the pharmacodynamic indices of mutant selection against multi-drug resistant Acinetobacter baumannii - Zhu, Shixing; Song, Chu; Zhang, Jiayuan; Diao, Shuo; Heinrichs, Tobias M.; Martins, Frederico S.; Lv, Zhihua; Zhu, Yuanqi; Yu, Mingming; Sy, Sherwin K. B. (Frontiers in Microbiology, 2022)
Amikacin and polymyxins as monotherapies are ineffective against multidrug-resistant A. baumannii at the clinical dose. When polymyxins, aminoglycosides, and sulbactam are co-administered, the combinations exhibit in vitro synergistic activities. The minimum inhibitory concentration (MIC) and mutant prevention concentration (MPC) were determined in 11 and 5 clinical resistant isolates of A. baumannii harboring OXA-23, respectively, in order to derive the fraction of time over the 24-h wherein the free drug concentration was within the mutant selection window (fTMSW) and the fraction of time that the free drug concentration was above the MPC (fT>MPC) from simulated pharmacokinetic profiles. The combination of these three antibiotics can confer susceptibility in multi-drug resistant A. baumannii and reduce the opportunity for bacteria to develop further resistance. Clinical intravenous dosing regimens of amikacin, polymyxin-B, and sulbactam were predicted to optimize fTMSW and fT>MPC from drug exposures in the blood. Mean fT>MPC were ≥60% and ≥80% for amikacin and polymyxin-B, whereas mean fTMSW was reduced to <30% and <15%, respectively, in the triple antibiotic combination. Due to the low free drug concentration of amikacin and polymyxin-B simulated in the epithelial lining fluid, the two predicted pharmacodynamic parameters in the lung after intravenous administration were not optimal even in the combination therapy setting.